Analisis Lingkungan Belajar Siswa Kelas 4 SD Gembong 02 Ditinjau Dari Teori Behavioristik - Agis Lestari Fatujiatin Ni'amah; Siti Masfuah; Deka Setiawan (PGSD Universitas Muria Kudus, 2023)
The purpose of this research is to analyze the learning environment of grade 4 SD Gembong 02 students in terms of behavioristic theory.The research method used is narrative qualitative. This research is focused on looking at the student learning environment in terms of behavioristic theory. The research was conducted at Gembong 02 Elementary School. The informants in this study were class IV children. Data collection techniques used are 1) documentation; 2) interviews; and 3) observation. In analyzing qualitative data, three stages were carried out, namely: data reduction, data display, and conclusion drawing/verification.The results of the study found that the learning environment influenced the learning behavior shown by students. The learning environment greatly influences the behavior shown by children when learning at school. A fun learning environment will show students who are active, passionate and enthusiastic when learning. Meanwhile, an unpleasant learning environment will tend to show students who are less active in the teaching and learning process and show poor learning behavior.Students feel happy and enthusiastic about participating in learning when students study in groups. When studying in groups, cooperation is needed to complete assignments so that students can do group work well. In carrying out assignments students can interact with their friends and collaborate so that they can stimulate students' abilities to behave well in learning.